E-COMMERCE TECHNOLOGY BASED BUSINESS DEVELOPMENT IN THE DIGITAL ERA: PESANTRENPRENEUR EXPERIENCE - Setiawan, Heri Cahyo Bagus; Ariyanto, Sudirman Rizki (STKIP PGRI Tulungagung, 2025)
This research aims to examine the development of an e-commerce technology-based business for red ginger products by the Alam Bumi Al-Quran Islamic Boarding School on the Shopee platform. The research method used is a qualitative approach using interviews, observation and document analysis. The research results show that utilizing Shopee features, such as product descriptions, quality photos, discount vouchers and flash sales, is effective in increasing product visibility and building consumer trust, which is reflected in positive reviews and customer satisfaction. Islamic boarding schools also integrate halal principles in product production and distribution, which is an added value compared to competitors. The marketing strategy involves collaborating with local communities, using Shopee's analytical features to adjust promotions, and utilizing social media to increase sales conversions. The active role of students in managing online stores is also a key success factor. The impact of e-commerce on the economic independence of Islamic boarding schools can be seen from the increase in sales volume which supports Islamic boarding school operations and provides practical experience for students in managing digital businesses. Despite facing challenges related to resistance to modernization, limited digital literacy, and technical obstacles, Islamic boarding schools overcome these with intensive training and the development of appropriate guidelines. This research provides insight for other Islamic boarding schools in adopting digital technology to support economic independence without ignoring religious (Islamic) values.